(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3U(B: (3aUd dCUGdI GdaYd aj GdJUQja RjO bHd aGA KdGKjI Edi KdGKI hbHd aGA QHGYjI Edi GKfJjf s
(3BNQgG (B:s
(3EPG de jcf eG gj ajg eVGakG Edi NHjQ MSH efGSH MQcJgG hbO JbOe dfG GdcdGe Ydi Pdc hbO GfJgi eG cJHfG ef gPG GdTQM ced GdSaQ GdYGTQ hHceGdg ced LejY GdOjhGf s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g```s
(3fSNI SGOSIs
(3HChdgG Jedc SfI (B986(3g``s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs